COMPLICATIONS OF PERCUTANEOUS CYSTOSTOMY AT TERTIARY HOSPITAL - Prabowo, Satria Adji Hady; Daryanto, Besut; Seputra, Kurnia Penta (Indonesian Urological Association, 2025)
Objective: This study aims to identify the complications associated with percutaneous cystostomy performed at tertiary hospital. Material & Methods: This study employed a retrospective descriptive design involving patients who underwent percutaneous cystostomy at Saiful Anwar General Hospital from January 2019 to December 2024. Data were collected by reviewing patient medical records, including information on average age, gender, diagnosis, and complications related to the procedure. Complications were classified into intra-procedural and post-procedural categories. This study was approved by the Health Research Ethic Commission of Saiful Anwar General Hospital No: 400/050/K.3/102.7/2025. Results: A total of 72 patients were included in the study (71 males, 1 female), with an average age of 58.58 years. Early complications observed in 7 patients included catheter obstruction in 6 patients (8.3%) and hematuria in 1 patient (1.4%). Late complications limited to surgical site infection, which occurred in 3 patients (4.2%). Conclusion: Percutaneous cystostomy is a safe and effective procedure with a low complication rate, making it a viable routine practice in clinical urology. Keywords: Percutaneous cystostomy, urinary retention, complications